Prevalence of High Serum Uric Acid in Patients with Acute Myocardial Infarction in Rajshahi Medical College Hospital (TAJ: Journal of Teachers Association, 2022)
Coronary artery disease is one of the commonest causes of death of our hospitalized patients. It has a number of risk factors such as age, sex, family history, smoking, hypertension, diabetes, dyslipidemia and obesity. Serum uric acid appears to be another risk factor found in several researches. This study was done to find out the prevalence of high serum uric acid in hospitalized acute myocardial infarction patients. This was a descriptive cross-sectional study carried out in department of Cardiology, Rajshahi medical college hospital from January 2015 to December 2016. 115 (one hundred fifteen) AMI patients were included. Baseline characteristics such as age, sex, body mass index, blood pressure, risk factors-hypertension, diabetes mellitus, smoking, family history of IHD, dyslipidemia was recorded. We measured serum uric acid of this patient at admission. Out of 115 patients, 83.5% were male and 16.5% were female. Among risk factors 65.2% had history of hypertension, 20.9% diabetes mellitus, 64.3% smoking, 16.5% family history of IHD and 47.8% dyslipidemia. Out of 115 patients, 35.7% had high serum uric acid and 64.3% had normal serum uric acid. There was no significant difference of confounding variables between high and normal serum uric acid level patients. We found larger number of AMI patients with high serum uric acid. So, high serum uric acid may be a risk factor for acute myocardial infarction.TAJ 2021; 34: No-2: 102-107